Perbandingan Kinerja Broiler Kandang Closed dan Open House dalam Satu Perusahaan Kemitraan yang Sama - Paly, Muhammad Basir (Jurnal Ilmu dan Industri Peternakan, 2023)
ABSTRACT Closed House (CH) and Open House (OH) systems can affect broiler productivity. This study aims to compare the performance of broilers raised in the CH and OH housing systems from the same core company. The contribution of this research is expected to provide additional information to previous studies and contribute to improving understanding of the performance comparison between broilers in CH and OH systems. The study was conducted in Takalar Regency, which is one of the broiler production centers using a partnership pattern. A survey method was used, targeting 3 samples each of CH and OH houses. Panel data from 11 production cycles were collected, resulting in 32 observations for OH and CH. The measured variables were mortality, feed conversion ratio (FCR), and performance index (PI). The data were analyzed using an independent t-test. The results showed significant differences in performance between OH and CH. OH had higher mortality, less efficient FCR, and lower PI compared to CH. This study concludes that CH housing is more productive than OH. To minimize risks in OH houses, it is recommended that farmers pay attention to microclimate control and improve feed nutrition. Keywords: broiler, mortality, FCR, performance index, closed house, open house